PENGARUH PEMBERIAN PUPUK ORGANIK CAIR AMPAS TAHU DAN BONGGOL PISANG TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SELEDRI (Apium graveolens L.) - Zainudin Maunte; Muh Iqbal Jafar; M Darmawan (Agropolitan, 2018)
This study aimed to determine the effect of liquid organic fertilizer from tofu cake and banana hump to the growth and production of celery. This study was conducted for 4 months in the village of Tenilo, sub-district of Limboto, Gorontalo regency. The research was using a randomized block design (RAK) consisted of 5 (five) treatment and 3 (three) replicates so that 15 units of the experiment, with different doses, namely P0 was a control, P1 was a dose of 30 ml/l of water tofu cake, P2 was a dose of 60 ml/l of water tofu cake , P3 was a dose of 30 ml/l water banana hump, and P4 was 60 ml/l water banana hump. The results showed that the provision of liquid organic fertilizer tofu and banana hump did not give any significantly effect on the plant height, number and the length of leaves.